NADZOR ONLINE DI ERA DIGITAL PERSPEKTIF MUHAMMAD ABDUH TUASIKAL - Mardhiyah, Radhiatan; Muhtadin, Sabilul (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Islam is a perfect religion. marriage is one of the sunnahs of the prophet that is recommended to his ummah. marriage in Islam has been arranged so beautifully including the matter of nadzor, nadzor is very permissible for those who are sure to proceed to a more serious level of marriage, nadzor also has manners that must be considered to avoid adultery. This research aims to find out the law related to online nadzor from the perspective of Muhammad Abduh Tuasikal in this digital era. The method used in this article is the literature study method using a qualitative approach that focuses on analysis which thinks comparatively based on the study of Muhammad Abduh Tuasikal. As for the results of research related to online nadzor, Muhammad Abduh Tuasikal argues that the law of online nadzor can be the same as the law of nadzor usually where online nadzor is carried out while still paying attention to the adab-adab that has been determined.